Bedaquiline-Loaded Solid Lipid Nanoparticles Drug Delivery in the Management of Non-Small-Cell Lung Cancer (NSCLC) - Shehla Nasar Mir Najib Ullah; Obaid Afzal; Abdulmalik Saleh Alfawaz Altamimi; Manal A. Alossaimi; Waleed H Almalki; Abdulaziz Alzahrani; Md. Abul Barkat; Tahani M. Almeleebia; Hanan Alshareef; Eman M. Shorog; Gyas Khan; Tanuja Singh; et al. (MDPI AG, 2023)
Non-small-cell lung cancer (NSCLC) mortality and new case rates are both on the rise. Most patients have fewer treatment options accessible due to side effects from drugs and the emergence of drug resistance. Bedaquiline (BQ), a drug licensed by the FDA to treat tuberculosis (TB), has demonstrated highly effective anti-cancer properties in the past. However, it is difficult to transport the biological barriers because of their limited solubility in water. Our study developed a UPLC method whose calibration curves showed linearity in the range of 5 ng/mL to 500 ng/mL. The UPLC method was developed with a retention time of 1.42 and high accuracy and precision. Its LOQ and LOD were observed to be 10 ng/mL and 5 ng/mL, respectively, whereas in the formulation, capmul MCM C10, Poloxamer 188, and PL90G were selected as solid lipids, surfactants, and co-surfactants, respectively, in the development of SLN. To combat NSCLC, we developed solid lipid nanoparticles (SLNs) loaded with BQ, whereas BQ suspension is prepared by the trituration method using acacia powder, hydroxypropyl methylcellulose, polyvinyl acrylic acid, and BQ. The developed and optimized BQ-SLN3 has a particle size of 144 nm and a zeta potential of (−) 16.3 mV. whereas BQ-loaded SLN3 has observed entrapment efficiency (EE) and loading capacity (LC) of 92.05% and 13.33%, respectively. Further, BQ-loaded suspension revealed a particle size of 1180 nm, a PDI of 0.25, and a zeta potential of −0.0668. whereas the EE and LC of BQ-loaded suspension were revealed to be 88.89% and 11.43%, respectively. The BQ-SLN3 exhibited insignificant variation in particle size, homogeneous dispersion, zeta potential, EE, and LC and remained stable over 90 days of storage at 25 °C/60% RH, whereas at 40 °C/75% RH, BQ-SLN3 observed significant variation in the above-mentioned parameters and remained unstable over 90 days of storage. Meanwhile, the BQ suspension at both 25 °C (60% RH) and 40 °C (75% RH) was found to be stable up to 90 days. The optimized BQ-SLN3 and BQ-suspension were in vitro gastrointestinally stable at pH 1.2 and 6.8, respectively. The in vitro drug release of BQ-SLN3 showed 98.19% up to 12 h at pH 7.2 whereas BQ suspensions observed only 40% drug release up to 4 h at pH 7.2 and maximum drug release of >99% within 4 h at pH 4.0. The mathematical modeling of BQ-SLN3 followed first-order release kinetics followed by a non-Fickian diffusion mechanism. After 24 to 72 h, the IC50 value of BQ-SLN3 was 3.46-fold lower than that of the BQ suspension, whereas the blank SLN observed cell viability of 98.01% and an IC50 of 120 g/mL at the end of 72 h. The bioavailability and higher biodistribution of BQ-SLN3 in the lung tumor were also shown to be greater than those of the BQ suspension. The effects of BQ-SLN3 on antioxidant enzymes, including MDA, SOD, CAT, GSH, and GR, in the treated group were significantly improved and reached the level nearest to that of the control group of rats over the cancer group of rats and the BQ suspension-treated group of rats. Moreover, the pharmacodynamic activity resulted in greater tumor volume and tumor weight reduction by BQ-SLN3 over the BQ suspension-treated group. As far as we are aware, this is the first research to look at the potential of SLN as a repurposed oral drug delivery, and the results suggest that BQ-loaded SLN3 is a better approach for NSCLC due to its better action potential.